A token-passing variable buffer model for a double-layered hierarchical WDM all-optical network - Tee, Elok Robert; Ramani, Ashwani Kumar; Selvadurai, Selvakennedy (Faculty of Computer Science and Information Technology, University of Malaya, 1998)
Presents a hierarchical all-optical network, employing wavelength division multiplexing for multiple channel transmission. A double-layered network with multiple sub-network implementation which provides for spatial wavelength reuse is considered. The piggybacked token-passing medium access protocol as a fair and non-contentious access scheme is studied for performance. The average delay in getting access to the network medium is determined from the semi-Markov process. The performance of the protocol model design with variable buffer sizes of the transmitter is analysed. It is shown from the double-layered hierarchical network that alternative route for data transmission can be implemented to improve on performance.